2022
DOI: 10.1186/s41181-022-00170-3
|View full text |Cite
|
Sign up to set email alerts
|

Core–shell structured gold nanoparticles as carrier for 166Dy/166Ho in vivo generator

Abstract: Background Radionuclide therapy (RNT) has become a very important treatment modality for cancer nowadays. Comparing with other cancer treatment options, sufficient efficacy could be achieved in RNT with lower toxicity. β− emitters are frequently used in RNT due to the long tissue penetration depth of the β− particles. The dysprosium-166/holmium-166 (166Dy/166Ho) in vivo generator shows great potential for treating large malignancies due to the long half-life time of the mother nuclide 166Dy and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 51 publications
3
3
0
Order By: Relevance
“…Therefore, the release of 109m Ag from the nanoparticles surface is not achievable. The same effect was also observed] with the 166 Dy/ 166 Ho in vivo generator deposited on the AuNPs surface (Wang et al 2022).…”
Section: Discussionsupporting
confidence: 68%
See 1 more Smart Citation
“…Therefore, the release of 109m Ag from the nanoparticles surface is not achievable. The same effect was also observed] with the 166 Dy/ 166 Ho in vivo generator deposited on the AuNPs surface (Wang et al 2022).…”
Section: Discussionsupporting
confidence: 68%
“…Studies conducted on in vivo generators, such as 103 Pd/ 103m Rh (Jensen et al 2020), 166 Dy/ 166 Ho (Wang et al 2022) and 212 Pb/ 212 Bi(Mirzadeh et al 1993), have demonstrated that a signi cant percentage of daughter radionuclides are liberated when chelators are employed to immobilize parent radionuclides. According to(Wang et al 2022…”
mentioning
confidence: 99%
“…Therefore, the release of 109m Ag from the nanoparticles surface is not achievable. The same effect was also observed] with the 166 Dy/ 166 Ho in vivo generator deposited on the AuNPs surface (Wang et al 2022 ).…”
Section: Discussionsupporting
confidence: 65%
“…Studies conducted on in vivo generators, such as 103 Pd/ 103m Rh (Jensen et al 2020 ), 166 Dy/ 166 Ho (Wang et al 2022 ) and 212 Pb/ 212 Bi (Mirzadeh et al 1993 ), have demonstrated that a significant percentage of daughter radionuclides are liberated when chelators are employed to immobilize parent radionuclides. According to (Wang et al 2022 ), the loss of daughter radionuclides was attributed to their de-excitation through the internal conversion, resulting in Auger electron emission, rather than to the recoil energy associated with the emission of ß - particles and neutrinos. As a result, the de-excited daughter radionuclides become highly charged what leads to electrons uptake from the surrounding chelator donor atoms.…”
Section: Discussionmentioning
confidence: 99%
“…The metal-ligand bonds are then broken as a result of the repulsive force between the positively charged atoms, and the daughter 166 Ho are released as free cations (Wang et al 2022).…”
Section: Discussionmentioning
confidence: 99%